Between a Rock and a hard Place Exploring Xenophobia and Voluntary Refugee Repatriation in South Africa - Görgmeier, Anne Juliane Ulrike (Department of Political Studies, 2022)
In October 2019, thousands of migrants, refugees and asylum-seekers took the streets in Cape Town and Pretoria to publicly express their dissatisfaction with their living and protection conditions in South Africa. The protests erupted one month after a series of xenophobic incidents in several urban areas. While Pretoria protests dissolved quickly, the Cape Town sit-in protests were only cleared in early 2020. In both cities, protesters claimed that poor living conditions, a lack of access to services and a constant fear of xenophobic violence and harassment had made it unbearable for them to sustain their lives in South Africa. Refugees and asylum-seekers therefore demanded improved protection and the resettlement to a safer third country. Third country resettlement forms one of the three durable solutions for refugee situation as defined by the UNHCR, besides local integration and voluntary repatriation. The South African government and the UNHCR, however, made it clear that third country resettlement could not be considered a solution for a majority of South Africa's refugees and asylum-seekers. With local integration equally failing the forced migrants in South Africa, voluntary repatriation may by default be their only option left. This study aims to explore the relation between xenophobia and voluntary refugee repatriation in a South African context. The fear of xenophobic violence that was expressed by the 2019 protesters raises doubt about South Africa's ability to meet the UNHCR's standards of refugee protection. At the same time, it compromises the protection measure of temporary local integration as outlined in the South African 1998 Refugee Act. This study will therefore explore he connection between conditions of asylum in South Africa and the decision-making process on repatriation by refugees and asylum-seekers. This study aims to contribute to better the understanding of conditions and dynamics that lead to spontaneous voluntary repatriation in refugee situations.